The Perissodactyla order: current knowledge about the lowland tapir, with particular focus on the Pantanal biome - Medici, Emília Patricia; Fantacini, Felipe Moreli (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
In the Pantanal of Brazil, the Perissodactyla order is represented by a single species: the lowland tapir (Tapirus terrestris) — the largest land mammal in Brazil. This species is listed as ‘vulnerable to extinction’ both nationally and globally. At the regional level, in the Pantanal, the tapir is listed as a near threatened species, considering that there are still significant populations in the biome — an estimated total of 30,000 individuals (14,000 sexually mature) — distributed in densities varying between 0.21 and 1.38 ind./km² in different sub-regions of the biome. The aim of this article was to compile the current knowledge about the species , — with emphasis on studies carried out in the Pantanal, — encompassing biological, ecological and health aspects, as well as present information on study methods and chemical restraint of free-living tapirs and highlight certain conservational challenges. This article brings new information about the tapirs of this biome. The information provided here can guide new studies, decision-making processes, and actions aimed at the conservation of tapirs and the Pantanal biome.